Introducing the HbAlc test for diagnosis, evaluation and longterm control of diabetesin patient with poridontal disease - Y; Soleymani-e Shayesteh (Tehran University of Medical Sciences, 1998)
Regard this, that majority of Diabetic patients that soffer from periodontal disease. Now, most of espesialist belive that these patients need to control their diabets with new methods for decreasing and controlling thier periodontal disease."nToday, most of physician, majority of periodontal for controlling of HbAlc Test."nThis test does not need to patient's cooperation and can do in any time."nThis test estimate,s the irreversible bound of hemogloboiin with glucose and from this point that"nhalf- life of red blood cell is 90-120 days the resuolt of this test is useable for every 5 months.